Complete mitochondrial genome of the crinoid echinoderm, Florometra species (Echinodermata, Crinoidea) - Sang-Eun Nam; Hyoung Sook Park; Jae-Sung Rhee (Mitochondrial DNA. Part B. Resources, 2020)
In this study, we report the sequence of the mitochondrial genome (mitogenome) of the crinoid echinoderm, Florometra species (Echinodermata, Crinoidea). The complete mitogenome of Florometra sp. was 15,792 base pairs long and was composed of 13 protein-coding genes (PCGs), two ribosomal RNA (rRNA) genes, 22 transfer RNA (tRNA) genes, and three regions of unassigned sequence (UAS) including one putative control region. Unique nucleotide composition, a clear positive bias for T with an apparent loss of C in PCGs as observed in the Crinoidea mitogenomes, was also seen in the Florometra sp. mitogenome (45% T, 12% C). Phylogenetic analysis with the concatenated nucleotide sequences of entire PCGs of echinoderms confirmed that Florometra sp. is highly related to F. serratissima within the family Crinoidea.